2022
DOI: 10.1186/s41155-022-00216-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and academic motivation in primary school students

Abstract: The role of emotions in the educational context is one of the lines of research that has generated most interest in recent years. This study explores the level of emotional intelligence (EI) and motivation towards studying of primary school (PS) students, as well as the relationship between both variables. For this, a quasi-experimental design has been used with an accidental sample of 541 students from public centers in the province of Pontevedra (Spain). The instruments used were a School Motivation Scale an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
6
9
0
Order By: Relevance
“…Participant 10 believed that motivation ''directs learners to set clear objectives for their language learning journey.'' The findings were in line with previous studies (Arias et al, 2022;Magnano et al, 2016) indicating that motivation significantly contributes to promoting learners' SLA, driving them to devote time and effort toward language proficiency for socio-economic growth.…”
Section: Motivationsupporting
confidence: 92%
See 1 more Smart Citation
“…Participant 10 believed that motivation ''directs learners to set clear objectives for their language learning journey.'' The findings were in line with previous studies (Arias et al, 2022;Magnano et al, 2016) indicating that motivation significantly contributes to promoting learners' SLA, driving them to devote time and effort toward language proficiency for socio-economic growth.…”
Section: Motivationsupporting
confidence: 92%
“…EI is typically characterized as the capacity to perceive, comprehend, and regulate one's personal emotions, in addition to empathizing with and managing others' emotions (Mayer, 2006). It comprises an array of competencies and skills fostering efficient emotional operations, including self-awareness (Kanesan & Fauzan, 2019;Killian, 2012), self-regulation (Laborde et al, 2014;Zhoc et al, 2018), empathy (Este´vez et al, 2019), social adeptness (Rani & Yadapadithaya, 2018;Schutte et al, 2001), and motivation (Arias et al, 2022;Magnano et al, 2016). This construct transcends conventional intelligence metrics spotlighting the emotional dimensions of human conduct and interaction (Aguilar-Luzo´n et al, 2014;Drigas & Papoutsi, 2018;Erol et al, 2020).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Estrada et al (2021) have proven that a connection exists between EI and involvement in education and that it has a beneficial influence on the students' academic success. Studies conducted on primary school students also showed a positive relationship between emotional intelligence and cognitive motivation (Arias et al, 2022). Authors have proven positive influence of emotions on cognitive processes, which is significant for the ability to solve tasks and facilitates the process of building a sense of competence.…”
Section: Discussionmentioning
confidence: 96%
“…The higher levels of emotional intelligence are even more valuable in protecting students’ motivation at this time. Previous studies have found that emotional intelligence may be strongly associated with learning motivation ( Arias et al, 2022 ; Mercader-Rubio et al, 2022a ), but this relationship needs to be further tested in a broader group of students. It would be valuable to further probe the mechanisms by which emotional intelligence affects learning among college students to better utilize the positive effects of emotional intelligence on education.…”
Section: Introductionmentioning
confidence: 94%